The Influence of Workplace Environment and Work Motivation on Job Performance: The Mediating Role of Employee Commitment Among Generation Z Workers - John Malt; Yasmine Nasution (Pusat P2M Politeknik Negeri Batam, 2025)
This study examines the influence of workplace environment and work motivation on job performance among Generation Z employees within Indonesia’s food and beverage (F&B) sector, with a particular focus on the mediating role of employee commitment. Employing a quantitative research approach, data were collected through structured online surveys and analyzed using structural equation modeling. The findings reveal that both workplace environment and work motivation significantly enhance employee commitment and directly improve job performance. Furthermore, employee commitment was found to partially mediate the relationships between workplace environment, motivation, and job performance, indicating its crucial role in sustaining organizational outcomes despite Generation Z’s typically lower organizational loyalty. The research highlights the importance of fostering flexible, supportive, and inclusive work environments tailored to the unique preferences of Generation Z employees. Additionally, intrinsic motivators such as personal growth opportunities and recognition were identified as key drivers of commitment and performance. This study contributes to the literature by integrating Herzberg’s Two-Factor Theory, the Job Demands-Resources Model, and Social Exchange Theory to provide a comprehensive framework for managing Generation Z in high-turnover service industries. Practical recommendations are offered for human resource strategies, while suggestions for future research call for exploration across broader industrial and cultural settings.